Pathogenic Bacterium Acinetobacter baumannii Inhibits the Formation of Neutrophil Extracellular Traps by Suppressing Neutrophil Adhesion - Kamoshida, Go; Kikuchi-Ueda, Takane; Nishida, Satoshi; Tansho-Nagakawa, Shigeru; Ubagai, Tsuneyuki; Ono, Yasuo (Frontiers in Immunology, 2018)
Hospital-acquired infections caused by Acinetobacter baumannii have become problematic because of high rates of drug resistance. A. baumannii is usually harmless, but it may cause infectious diseases in an immunocompromised host. Although neutrophils are the key players of the initial immune response against bacterial infection, their interactions with A. baumannii remain largely unknown. A new biological defense mechanism, termed neutrophil extracellular traps (NETs), has been attracting attention. NETs play a critical role in bacterial killing by bacterial trapping and inactivation. Many pathogenic bacteria have been reported to induce NET formation, while an inhibitory effect on NET formation is rarely reported. In the present study, to assess the inhibition of NET formation by A. baumannii, bacteria and human neutrophils were cocultured in the presence of phorbol 12-myristate 13-acetate (PMA), and NET formation was evaluated. NETs were rarely observed during the coculture despite neutrophil PMA stimulation. Furthermore, A. baumannii prolonged the lifespan of neutrophils by inhibiting NET formation. The inhibition of NET formation by other bacteria was also investigated. The inhibitory effect was only apparent with live A. baumannii cells. Finally, to elucidate the mechanism of this inhibition, neutrophil adhesion was examined. A. baumannii suppressed the adhesion ability of neutrophils, thereby inhibiting PMA-induced NET formation. This suppression of cell adhesion was partly due to suppression of the surface expression of CD11a in neutrophils. The current study constitutes the first report on the inhibition of NET formation by a pathogenic bacterium, A. baumannii, and prolonging the neutrophil lifespan. This novel pathogenicity to inhibit NET formation, thereby escaping host immune responses might contribute to a development of new treatment strategies for A. baumannii infections.